TILBAGE TIL GADEN: Børn og unges liv på gaden i Nairobi - Molding, Malene (Tidsskriftet Antropologi, 1998)
Malene Molding: Back to the Street: Young People Living in the Streets of Nairobi The article deals with people who live and work on the streets of Nairobi, Kenya. It is based on fieldwork conducted in 1995-1996 by the author, who at that time was working at a rehabilitation centre for Street giris. The article aims to identify pull-factors, i.e. factors which, to young people, make Street life appear as an attractive alternative to other apparently desirable lifestyles. Thus, it differs in focus from other studies aiming to identify and explain so-called push factors, i.e. factors such as political, economic or social conditions that initially cause young people to choose to leave home and take to the streets. Inspired by sociologist Pierre Bourdieu, the author regards Street life as a lifestyle that unfolds in a social field characterised by specific codes of conduct and competitive social positions of symbolic Capital. By introducing the concept of “Street life expertise” and discussing its linkage to motivation and identification, the author argues that Street life appears attractive to people who have established social com- children’s bodily experiences, are shown to be in conflict with the children’s perspectives.